Perancangan Program Kerja dan Pendampingan Numerasi untuk Peserta Didik SD Yapita Kota Surabaya - Evi Yuliawati; Benita Amadea Nathania; Dela Reza Neo Wardiana; Musyasaroh Musyasaroh; Ervika Aprilia Rahmawati Buchori; Siti Nabilah; Clora Widya Brilliana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Mastery of numeracy by elementary school student is very important because it will be the foundation for them in understanding more complex mathematical concepts in the future. The Teaching Campus Program, which is part of the Independent Learning Independent Campus (MBKM) policy, also plays a role in improving numeracy learning for elementary school student. This study aims to design a strategy to determine a work program to help students improve their numeracy skills at SD Yapita Surabaya in the Teaching Campus Program. The data were collected using observation and assessment tests. This analysis resulted in numeracy work programs such as Math Cobra Sprint, Additional Lessons, Teams Games Tournaments, Count Your Cookies!, and Multiplication Wheel. After conducting various numeracy work programs, teaching activities have shown an improvement in the learning process at SD Yapita Surabaya. Students become more interested in learning and more open to critical thinking when using learning media, both technology-based and non-technology-based. The work program has increased students' interests and skills, especially numeracy.